(untitled) (AYUSHDHARA, 2024)
Background and Objectives: Optic atrophy is an end stage condition where the optic nerve degenerates and leads to symptoms like vision loss. Objective of the present study was to evaluate the effect of Shatahwadi ghrita in the management of optic atrophy. Methods: 32 patients filling the inclusion criteria of optic atrophy were randomly selected for the study. Source of the data - Patients were selected from OPD and IPD of Shalakyatantra, S.D.M. College of Ayurveda and Hospital, Hassan. Shatahwadi ghrita was administered as Aschyotana, Pratimarsha nasya and Ghrita pana. Clinical signs and symptoms were given suitable scores according to its severity and assessed based on pre and post data gathered through pre- designed research proforma. The results having ‘p’ value less than <0.01 was considered to be statistically significant in this study. Observation & Results: The results were statistically analysed; it showed significant changes in contrast sensitivity, visual efficiency and retinal nerve fibre layer thickness. Interpretation And Conclusion: 1. Shatahwadi ghrita is found effective in the management of optic atrophy. 2. All the patients responded to the given treatment without any complications. 3. In most of the cases improvement found in contrast sensitivity, visual efficiency and retinal nerve fibre layer thickness.